Konflik Agraria di Desa Pandumaan-Sipituhuta Kabupaten Humbahas - PURBA, FREDY YOHANNES (Politeia: Jurnal Ilmu Politik, 2014)
Land conflict and agrarian reform is the most interesting issues in Indonesia. As we know a lot of people in Indonesia still lives on farms. There is no exception in Sumatera Utara Province. There are many land conflicts here. This study is the study of the problems of agrarian conflict in the Village District Pandumaan-Sipituhuta Humbang Hasundutan (Humbahas) Regency. The focus is about how the process of resolving issues of land conflict in the village Pandumaan-Sipituhuta. The findings of this study, among others, there are three important things to be problems in the agrarian conflict Sipituhuta - Pandumaan village. First, the eucalyptus forest planting activities in forest communities frankincense; Second, the weak role of district govern-ment Humbang Hasundutan; Third, problem-solving solutions. This study is using conflict approach. The data collection is using field research. The method used is a qualitative method that is intended to describe an event in more detail.Keywords: Conflict, land reform, indigenous lands.